Analysis of User Readiness Level of E-Government Using Stope Framework - Windi Eka Yulia Retnani; Ricky Freydinansa A. P; Beny Prasetyo (IAES Indonesia Section, 2019)
The Village Information Administration System (VIAS) is one of the many IT service implemented by the Bondowoso district. The successful implementation of an IT service like VIAS can be seen from the extent to which the level of readiness of the user adopts the service. To determine the extent to which the user readiness level can be performed a measurement using the relevant method. STOPE Framework is one of the method that can be used to measure the extent to which the IT service user readiness and can provide recommendations based on the result of the evaluation. Measurement of user readiness in this study using STOPE Framework and determination of a 4 point scale based readiness level issued by the Centre for International Development/CID (Harvard Cyber Law). Data analysis result show VIAS user readiness level is at level 4(completely ready). This indicates that the VIAS user is ready to use the Village Information Administration System based on approach using STOPE Framework.